ESCHERICHIA COLI CONTAMINATION IN HOUSEHOLD DRINKING WATER AND STUNTING IN CHILDREN UNDER FIVE : A CORRELATIONAL STUDY IN PADANG PANJANG - Neila Sulung; Ronny Afdinal (LLDIKTI Wilayah X, 2025)
Background: Stunting is a significant nutritional issue currently faced by many toddlers. The source, quality, and management of water consumed by children can be factors that influence stunting. Objective: This study aims to analyze the relationship between the source, physical quality, bacteriological quality, management behavior, and Escherichia coli contamination in household drinking water with stunting in children under 5 years old. Methods: This research uses a quantitative design with a cross-sectional approach. The sample consists of 69 households with toddlers, selected using proportional random sampling technique. Data were analyzed bivariately using the chi-square test. Results: There are three independent variables that have a significant correlation with the dependent variable, namely the bacteriological quality of household drinking water, household drinking water management behavior, and Escherichia coli contamination in household drinking water. Escherichia coli contamination is the most dominant factor (OR 86.667, CI: 9.389-800.005). Conclusion: This study concludes that there is a significant correlation between Escherichia coli contamination in drinking water and stunting in toddlers. It is hoped that through this research, the public can understand and apply the principles of handling and managing safe drinking water at the household level.